Revendications religieuses sur les aires protégées chez les Gourmantché du Burkina Faso - Alexis Kaboré (VertigO)
Most of the protected areas (classified forests, national parks and reserves of faune…) are old territories of communities settled in their peripheries. These populations are organized following a process of the territory’s construction which, most often, has a religious dimensions. In sub-Saharan African societies, the sacrificial altars constitute the greatest mark of such a representation of the space. Keeping on offering sacrifices to the powers associated to these altars is, for the populations, on obligation. Thus, they have to go to the altar even when it is located inside the classified area. The impossibility of going back to the sacrificial sites due to the constraints of the protected area is one of the main causes of contestation opposed by the populations of the periphery. How do societies characterized by populations’ mobility solve the contradictions between movings (voluntary or forced) of people and “fixedness” of worship places? As far as Gourmantché are concerned, the sacrificial system has within itself solutions to accede the altars that the populations still sollicitate: the altar is to be displaced, reproduced or offered sacrifices from far away. Since the, how can we report the so strong resistances to the interdiction of access to these spaces, including for the perpetuation of the sacrifice rites. The goal of this article is to analyse the meaning of resistances manifested by administrative injunctions’ round going pratices and the critical speeches developed by the populations about the access to their worship places.